2014
DOI: 10.1111/pai.12275
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial basement membrane thickening is related to TGF‐Beta 1 expression in children with chronic respiratory diseases

Abstract: Increased BM thickness and number of TGF-β1 positive epithelial cells were found in children with asthma, CF and PCD. The number of TGF-β1 positive cells correlated positively with the BM thickness in all groups. We suggest that this might be a common generic feature of bronchial remodelling in chronic respiratory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Initial changes leading to remodeling, including thickness of the basement membrane (BM), subepithelial deposition of laminin, and collagen IV in the BM, have been defined as starting at less than 4 years of age in asymptomatic children predisposed to asthma . Similar structural changes in bronchial mucosa have been described in children with asthma, cystic fibrosis, and primary ciliary dyskinesia . This might suggest a common feature of bronchial remodeling in chronic respiratory diseases.…”
Section: Origins Of Asthma and Allergic Rhinitismentioning
confidence: 98%
“…Initial changes leading to remodeling, including thickness of the basement membrane (BM), subepithelial deposition of laminin, and collagen IV in the BM, have been defined as starting at less than 4 years of age in asymptomatic children predisposed to asthma . Similar structural changes in bronchial mucosa have been described in children with asthma, cystic fibrosis, and primary ciliary dyskinesia . This might suggest a common feature of bronchial remodeling in chronic respiratory diseases.…”
Section: Origins Of Asthma and Allergic Rhinitismentioning
confidence: 98%
“…Despite the existence of multiple clinical endotypes, most forms of asthma exhibit a dysregulated epithelial barrier. Asthmatic epithelium is characterized by an increase in basal and goblet cells 18 and a decrease in terminally differentiated ciliated cells, frequently accompanied by basement membrane thickening 19, 20 and epithelial shedding with the formation of Creola bodies consisting of clusters of shed epithelium (even in mild forms of disease) 2123 . Disruption of epithelial tight and adherens junctions is typical for asthma, with marked loss of E-cadherin 24 and claudin-18 25 .…”
Section: Barrier Defects In Type 2 Diseasesmentioning
confidence: 99%
“…TGFis also expressed in eosinophils, one of the key in ammatory cells in asthma, and its expression therein is upregulated in severe asthma 20,21 . Recent reports also indicated that TGF-expression correlates with the thickening of the basement membrane in children with asthma, even though these patients were using inhaled corticosteroids 22 . In concordance with this and as we demonstrated in this study, TGF-might contribute to the pathogenesis of airway remodeling through the upregulation of endothelin-1 expression in the bronchial epithelium.…”
Section: Discussionmentioning
confidence: 99%